THE ESTIMATION OF FATIGUE LIMIT OF 2D PLAIN-WOVEN T300 CARBON-FIBER/SIC MATRIX COMPOSITE - GAO DaiYang; YAO WeiXing; WU Tao (Jixie qiangdu)
The fatigue property data of 2 D plain-woven T300 carbon-fiber/SiC matrix composite material, which was published in literatures since 1990, was collected and categorized. The fitting of the total life S-N curve was conducted on the collected data. According to the shape parameter a of the S-N curve, T300 C/SiC material is classified into 3 categories. It is shown in the curve fitted results that the shape parameter a in the total life S-N curve represents the toughness of the material, in which case the larger parameter a is, the tougher the material is. Meanwhile the dimension parameter b represents the fatigue crack propagation rate, in which case the smaller parameter b is, the more sensitive to stress the fatigue damage is. On the basis of the fitted data, it is concluded that the endurance limit of 2 D plain-woven T300 carbon-fiber/SiC matrix composite material is approximately 70% of its strength.